STRATEGI PENINGKATAN PEROLEHAN SISA HASIL USAHA (SHU) KOPERASI DI KOTA BANDA ACEH - Reza Septian Pradana (Jurnal Ekonomi-Qu, 2019)
This study aims to formulate the strategy done by cooperatives in Banda Aceh City through identifying determined factors of cooperatives’ profit. This study uses multiple regression analysis. The result of estimation by using multiple regression analysis shows that equity capital and business volume of cooperatives significantly give positive influence to profit of cooperatives. Debt capital of cooperatives and the number of cooperatives’ members insignificantly influent to profit of cooperatives. So, the strategy that can be done to increase profit of cooperatives in Banda Aceh City is increasing equity capital and business volume of cooperatives.